Profile of patients with gastrointestinal bleeding in reference service during the Sars- Cov-2 pandemic (Covid-19) (Brazilian Journal of Health Research, 2023)
Introduction: Digestive Bleeding (DB)) is an important cause of morbidity, especially the upper gastrointestinalbleeding. During the Sars-CoV-2 pandemic, DB was one of the gastrointestinal symptoms described. Objective: To analyze the profile of patients hospitalized for DB along the 95-day period of pandemic and comparison between infection or not by COVID 19. Methods: Retrospective analysis of medical records of hospitalizations for BD at the University Hospital Cassiano Antonio Moraes. The clinical profile, presentation of the condition, hemodynamic variables, endoscopic findings and Sars-Cov-2 infection were characterized. Results: In the analyzed period, 251 hospitalizations were registered due to BD and in 21 COVID was present. The average age was 60.04 years, one third were male, with an average of 9.2 days in hospital, average hemoglobin of 8.17 mg/dL, duodenal ulcer was the main cause of DB, followed by esophageal varices. Rebleeding occurred in 22 cases and 42 patients died. Conclusion: DB is a clinical complication with high morbidity and high mortality risk. During the period of the COVID 19 pandemic, an increase in mortality was observed among infected patients.
Keywords: Gastrointestinal hemorrhage; Peptic ulcer; Esophageal and Gastric Varices; Covid-19